Mapping Digital Literacy of Elementary School Teachers in the Era of Digital Native Generation - Purnomo, Eko; Darmawati; S. Nadra, Wawan (International Journal of Elementary Education, 2024)
Teachers are currently challenged to adapt to the digital native generation, requiring them to effectively utilize digital technology in designing engaging learning experiences. This study aims to assess the digital literacy levels of elementary school teachers and analyze the relationship between digital literacy and variables such as age, years of service, and employment status. A quantitative research method with a survey approach was employed. The study involved 141 teachers selected through random sampling. Data were collected using a questionnaire instrument comprising four modified digital literacy indicators: internet searching, hypertext navigation, content evaluation, and knowledge assembly. Data analysis was conducted using Microsoft Excel, while correlation testing utilized Spearman’s technique. The findings revealed that the digital literacy of elementary school teachers across four districts was moderately good, as reflected in maximum score presentations at levels 4 and 5. In practice, some teachers were able to design digital teaching materials, though many faced challenges due to inadequate infrastructure support. Correlation tests indicated significant relationships between hypertext navigation, content evaluation, and knowledge assembly with teachers' digital literacy levels. The study concludes that schools should enhance infrastructure support for digital literacy implementation, and teachers need additional training to effectively address the demands of teaching in the digital native era.